2015
DOI: 10.1093/gastro/gov027
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision and augmented reality in gastrointestinal endoscopy: Figure 1.

Abstract: Augmented reality (AR) is an environment-enhancing technology, widely applied in the computer sciences, which has only recently begun to permeate the medical field. Gastrointestinal endoscopy—which relies on the integration of high-definition video data with pathologic correlates—requires endoscopists to assimilate and process a tremendous amount of data in real time. We believe that AR is well positioned to provide computer-guided assistance with a wide variety of endoscopic applications, beginning with polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…Colonoscopy is the gold-standard diagnostic tool for colorectal cancer (CRC) and precancerous lesions. However, the adenoma miss-rate (AMR) ranges from 6% to 27% [1]. It is noteworthy that precancerous lesions with a flat morphology, smooth surface, indistinct boundaries or isochromatic with background are more susceptible to be missed [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonoscopy is the gold-standard diagnostic tool for colorectal cancer (CRC) and precancerous lesions. However, the adenoma miss-rate (AMR) ranges from 6% to 27% [1]. It is noteworthy that precancerous lesions with a flat morphology, smooth surface, indistinct boundaries or isochromatic with background are more susceptible to be missed [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that with a second party observing the monitor synchronously during colonoscopy, polyp detection rate could be improved by means of addressing the unrecognized polyps within the visual field [1]. However, in comparison with polypoid lesions, to detect LSTs and SSA/Ps is a more challenging task, it is likely that adding an additional human observer would not completely overcome the challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A denomas are routinely missed during colonoscopy by individual endoscopists. 1 Although colonoscopy remains the gold standard for screening cancer and precancerous lesions in the colon, 2 colonoscopy can be technically demanding because it requires both manipulation and observation at the same time, and there is significant variation in how colonoscopy is performed and how lesions are detected between individual endoscopists.…”
mentioning
confidence: 99%
“…Such lesions could be better exposed by means of high-quality bowel cleansing, endoscopic cameras with wider viewing angles, and meticulous mucosal inspection techniques. 1 However, the adenoma miss rate (AMR) still ranges from 6% to 41% using white-light colonoscopy. 1,3 Studies using full-spectrum colonoscopy (FUSE), which provides 330 angle of view, show an AMR of between 7.0% 4 and 20.5%.…”
mentioning
confidence: 99%
“…After that, there were more CAD applications based on specific databases [8][9][10][11], but the number of images in these databases was limited, mostly less than 20. In 2015, Tyler Berzin's team put forward the product idea of AI assisted endoscopy diagnosis [12].…”
Section: Introductionmentioning
confidence: 99%